2020
DOI: 10.1186/s43161-020-00002-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whole body vibration versus resistive exercise on premenstrual symptoms in adolescents with premenstrual syndrome

Abstract: Background: Premenstrual syndrome (PMS) is a cyclic disorder that affects social activities, interpersonal relationship, and educational productivity of adolescents. Therefore, this study aimed to compare the effect of whole body vibration (WBV) and resistive exercise on premenstrual symptoms in adolescents with PMS. Methods: Sixty adolescents, aged 16-19 years and with body mass index > 19.9 kg/m 2 , participated in the study. They were randomly assigned to three groups equal in number. Control group received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 30 publications
(33 reference statements)
1
34
1
Order By: Relevance
“…Likewise, Goldfield et al [ 58 ] showed an unclear risk of bias for dropout bias. On the other hand, the rest of the studies [ 56 , 57 , 60 , 61 , 62 ] showed a low risk of bias for all domains. Full details of each study and domain are presented in Figure 3 and Figure 4 .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Likewise, Goldfield et al [ 58 ] showed an unclear risk of bias for dropout bias. On the other hand, the rest of the studies [ 56 , 57 , 60 , 61 , 62 ] showed a low risk of bias for all domains. Full details of each study and domain are presented in Figure 3 and Figure 4 .…”
Section: Resultsmentioning
confidence: 98%
“…Besides, one article evaluated mental health (emotional, psychological, and social well-being) [ 64 ], which is commonly associated with psychosocial anxiety disorders and depression [ 65 ]. On the other hand, strength training was reflected through the following intervention modes: CrossFit Teens™ [ 64 ], concurrent training (CT) combining aerobic and strength exercises [ 56 , 57 , 58 , 61 , 63 ], vibration platform strength training [ 60 , 62 ], and conventional strength training [ 58 , 59 , 62 ]. The characteristics and type of strength training protocol of the studies selected in this systematic review and meta-analysis are presented in Table 1 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It affects 20-80% of females of reproductive age (2). The syndrome has severe physical, cognitive, psychological and somatic symptoms that influence activities of daily living, inter-personal relations, social life, work efficiency and educational productivity (3). The precise pathology of PMS is unknown.…”
Section: Introductionmentioning
confidence: 99%